Apie mįslingąją Wolfenbüttelio postilę ir jos kalbą - Zinkevičius, Zigmas (Baltistica, 2002)
ON THE MYSTERIOUS WOLFENBÜTTEL POSTILLA AND ITS LANGUAGE The findings based on the dialectological analysis of the language of the Postilla suggest distinguishing between two basic dialect sources, namely Southern Aukštaitish and Western Aukštaitish. Moreover, a significant influence of the Žemaitish dialect and traces of the Curonian (Lith. kuršiai or kuršininkai) language can also be seen. The primary source is the Southern Aukštaitish dialect, the geographical extension of which must have been to the south-western part of the present day area of this dialect and it may have reached south-eastern Belorussia, where Lithuanian is no longer spoken today. The unknown translator of the Postilla into Lithuanian must have been born in this area and only later he moved to Prussia. As the Southern Aukštaitish dialect was not used in Prussia, the translation was not acceptable and someone started to adapt the text to the Western Aukštaitishdialect (especially to its southern variety). The local Lithuanian, Jonas Bretkūnas, might have undertaken this task. The Žemaitish dialect data come from the variety of Žemaitish used in Prussia but not from Žemaitish spoken in the state of Lithuania. The presence of the given data might have resulted from the fact that the person responsible for the adaptation of the language of the Postilla was influenced by the Žemaitish dialect. Jonas Bretkūnas was the person. The same explanation is applicable to the occasional Curonian data, which are related to Prussia where Curonian was spoken at that time.